The age of wonder how the Romantic generation discovered the beauty and terror of science - Holmes, Richard 1945- (Harper Press, 2008)
The Age of Wonder' is Richard Holmes' first major work of biography for a decade. It has been inspired by the scientific ferment that swept through Britain at the end of the 18th century, and which Holmes now radically redefines as 'the revolution of Romantic Science."